(untitled) (Annals of Medical Research, 2021)
Aim: The aim of our study is to evaluate the cases with invasive mucinous adenocarcinoma (IMA) detected separately from lung adenocarcinoma in the 2015 WHO classification and to associate the clinicopathological findings and evaluate their prognostic significance based on computed tomography (CT) findings. Materials and Methods: The materials of patients who underwent resection from January 1 2011 to June 31 2019 at our hospital were reviewed after archive screening and those belonging to the Invasive mucinous adenocarcinoma group were determined according to the WHO 2015 classification. Clinical and radiological data of the cases were collected. Tumors were classified as solitary or pneumonic type based on CT findings, and the data obtained were compared statistically. Results: Based on CT findings (pneumonic and solitary), pathological T stages were significantly different between the two groups. Based on CT findings, pneumonic type-IMA was associated with a more advanced stage (p<0.001) and worse prognosis than solitary type-IMA. In addition, while pneumonic type IMA has a higher rate of aerogenous spread (STAS), there was no statistically significant relationship between other clinicopathological findings. Conclusion: Invasive mucinous tumors can be created with different CT images. Based on CT findings, evaluation of invasive mucinous adenocarcinoma before surgical resection may be useful in predicting prognosis.